The demand for healthcare in Singapore. - Ong, Shi Ting. (2008)
For the past few decades, the demand for healthcare in Singapore has been rising steadily. This trend is likely to continue, so it is important to identify factors that contribute towards this phenomenon. This paper uses time series data to determine the demand for healthcare over time. Consistent with previous studies, the results from our log-linear regression identified price of healthcare, prices of other goods and services, age, and education as significant factors influencing the demand for healthcare in Singapore.